2013
DOI: 10.1371/journal.pone.0060157
|View full text |Cite|
|
Sign up to set email alerts
|

Retrospective Analysis of Prognostic Factors in 205 Patients with Laryngeal Squamous Cell Carcinoma Who Underwent Surgical Treatment

Abstract: ObjectivesTo investigate the most important factors affecting the prognosis of the patients with squamous cell carcinoma (SCC) of the larynx.MethodsBased on the clinical and follow-up data, 205 patients with SCC of the larynx receiving total laryngectomy, partial laryngectomy, or CO2 laser surgery in GuangDong General Hospital were retrospectively analyzed. A survival analysis was performed by the Kaplan-Meier method and a multivariable analysis of prognostic factors was carried out using the Cox proportional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
83
2
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(95 citation statements)
references
References 21 publications
6
83
2
4
Order By: Relevance
“…[23] Similarly, the 3-year overall survival rates in the current study was 69% for all patients, 83% for early-stage, and 61% for late-stage disease .…”
Section: Discussionsupporting
confidence: 66%
“…[23] Similarly, the 3-year overall survival rates in the current study was 69% for all patients, 83% for early-stage, and 61% for late-stage disease .…”
Section: Discussionsupporting
confidence: 66%
“…In general, the supra and subglottic cancers have worse prognosis than glottic cancers, which 5-year survival is 82% for early stages possibly related to early detection. 15 Moreover, PS, 12,16 node invasion 16,17 and localization 12 are prognostic factors for disease-free survival in conjunction with pathologic stage (pT), 17 surgical resection margins 16 and pretreatment tracheotomy. 18 Moreover, T4 primary extension and more than 2 cm tumoral invasion of the base of the tongue were shown to be associated with increased salvage laryngectomy in the Veterans study.…”
Section: Introductionmentioning
confidence: 99%
“…CD44+/CD133+ cells obtained from human laryngeal primary carcinoma cells exhibited elevated levels of beta1-integrin (also known as CD29) [24]. Its expression was also significantly associated with cervical lymph node metastasis, T stage, and histologic differentiation [68].…”
Section: Other Potential Cancer Stem Cell Biomarkersmentioning
confidence: 99%
“…When CD44 and CD133 positive cells (CD44+/CD133+) were injected to mice, they produced significantly larger tumors compared to those produced from other cell populations. CD44+/CD133+ cells, with stronger invasive potential, were also found to express several other stem cell markers [24]. In a recent study, Suer et al [21] investigated the CSC potential of CD133+ cells isolated from freshly resected LCa specimens and found that CD133+ cells strongly express stemness genes such as SOX2, OCT4 and KLF4.…”
mentioning
confidence: 99%